2017
DOI: 10.1136/bmjopen-2017-018091
|View full text |Cite
|
Sign up to set email alerts
|

Risks for comorbidity in children with atopic disorders: an observational study in Dutch general practices

Abstract: ObjectiveThis study aimed to investigate both atopic and non-atopic comorbid symptoms and diseases in children with physician-diagnosed atopic disorders (atopic eczema, asthma and allergic rhinitis).MethodsAll children aged 0–18 years listed in a nationwide primary care database (the Netherlands Institute for Health Services Research-Primary Care Database) with routinely collected healthcare data in 2014 were selected. Children with atopic disorders were matched on age and gender with non-atopic controls withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 39 publications
2
25
2
Order By: Relevance
“…Alopecia areata frequently shows the strongest association [46,47], which would be consistent with the higher prevalence of hair and hair follicles diseases found in our sample. Psoriasis was also more prevalent in our population with AD, as previously described by Pols et al [40]. The association of central obesity with AD was already reported, especially in women [16].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Alopecia areata frequently shows the strongest association [46,47], which would be consistent with the higher prevalence of hair and hair follicles diseases found in our sample. Psoriasis was also more prevalent in our population with AD, as previously described by Pols et al [40]. The association of central obesity with AD was already reported, especially in women [16].…”
Section: Discussionsupporting
confidence: 90%
“…Regarding visual impairment, the third most frequent comorbidity in our study (7.8%), Pols et al [40] found an association between AD (OR (95% CI)) and blepharitis/styes/chalazion (1.53 (1.29-1.81)), infectious conjunctivitis (1.53 (1.20-1.81)), and allergic conjunctivitis (1.99 (1.59-2.49)) after analyzing a nationwide primary care database of children in the Netherlands. However, since the exact prevalence of each of the diagnoses included in the visual impairment EDC was unavailable, we were unable to contrast their results with our own.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Children who have one atopic disorder are at risk of developing other atopic disease(s). 32 Subsequently, more intense physical symptoms in comorbidity are likely to influence parental distress and poorer family functioning. In addition, it seems that parental functioning and wellbeing in our study were impaired to a lesser extent if the child affected with AD was older.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms include recurrent episodes of wheeze, cough and breathlessness 3. Asthma in children is associated with significant comorbidity, for example, other airway symptoms and/or (infectious) diseases 4. Moreover, the symptoms may have a considerable impact on the quality of life of children with asthma and their parents, as well as on healthcare costs.…”
Section: Introductionmentioning
confidence: 99%